2017
DOI: 10.3389/fpsyg.2017.00279
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing As an Adjunct to Periodontal Therapy—A Systematic Review

Abstract: Aim: Periodontal therapy is highly dependent on a patient's long-term adherence with regard to oral hygiene, diet, and regular check-ups at the dentist. Motivational Interviewing (MI) is a client-centered, directive method for encouraging a patients' behavioral health change. The aim of this systematic review was to reveal the effects of MI as an adjunct to periodontal therapy.Methods: Three databases (PubMed, Cochrane Library, and Web of Science) were reviewed for randomized controlled clinical trials. Articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
60
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 50 publications
0
60
1
2
Order By: Relevance
“…Moreover, patients subjected to the individually tailored programme showed higher self‐efficacy beliefs for maintaining their attained level of oral hygiene behaviour. However, due to the application of MI embedded in a combination with other components of the behavioural intervention, the specific effects of MI on the results are difficult to evaluate and hence, from a methodological point of view, studies designed to evaluate MI per se are warranted …”
Section: Introductioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Moreover, patients subjected to the individually tailored programme showed higher self‐efficacy beliefs for maintaining their attained level of oral hygiene behaviour. However, due to the application of MI embedded in a combination with other components of the behavioural intervention, the specific effects of MI on the results are difficult to evaluate and hence, from a methodological point of view, studies designed to evaluate MI per se are warranted …”
Section: Introductioncontrasting
confidence: 56%
“…The conclusions drawn were that MI is effective in all these health domains, but that additional research is needed and particularly in the oral health arena where only four studies were identified. More recent systematic reviews have focused specifically on the emerging field of MI in dental practice. Gao et al concluded that the reviewed RCT showed varied success of MI in improving oral health and that the potential of MI, especially on improving periodontal health, remains controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eight articles in this review, only two use an MI-based approach and both were included in the review by Gao et al in 2013, 2 thus not contributing new knowledge on the theme. Kopp et al 5 included five articles in their analysis, of which only one differed from those in the review by Gao et al 2 All the studies obtained a good quality assessment. Two articles showed no influence of MI on the clinical results of patients, while the other three demonstrated that the use of MI as an adjunct to periodontal treatment resulted in significantly higher clinical outcome values compared to controls or improvement in self-efficacy for dental hygiene.…”
Section: Referencesmentioning
confidence: 99%
“…Two reviews were published on the theme between late 2016 and early 2017. Kay et al 4 conducted a systematic review to analyze evidence of the use of MI in oral health, while Kopp et al 5 proposed a systematic review centered on outcomes of interest specific to periodontal health. Despite its hopeful conclusion concerning the application of this approach in oral health, the results of the review by Kay et al 4 are questionable in that it includes studies that do not use MI to change behavior and does not include randomized controlled trials (RCTs) which provide sound evidence on the topic.…”
Section: Referencesmentioning
confidence: 99%